Regulators of phagocytosis as pharmacologic targets for stroke treatment - Cheng, Jian; Wang, Wei; Xia, Yiqing; Li, Yi; Jia, Jia; Xiao, Guodong (Frontiers in Pharmacology, 2023)
Stroke, including ischemic and hemorrhagic stroke, causes massive cell death in the brain, which is followed by secondary inflammatory injury initiated by disease-associated molecular patterns released from dead cells. Phagocytosis, a cellular process of engulfment and digestion of dead cells, promotes the resolution of inflammation and repair following stroke. However, professional or non-professional phagocytes also phagocytose stressed but viable cells in the brain or excessively phagocytose myelin sheaths or prune synapses, consequently exacerbating brain injury and impairing repair following stroke. Phagocytosis includes the smell, eating and digestion phases. Notably, efficient phagocytosis critically depends on phagocyte capacity to take up dead cells continually due to the limited number of phagocytes vs. dead cells after injury. Moreover, phenotypic polarization of phagocytes occurring after phagocytosis is also essential to the proresolving and prorepair properties of phagocytosis. Much has been learned about the molecular signals and regulatory mechanisms governing the sense and recognition of dead cells by phagocytes during the smell and eating phase following stroke. However, some key areas remain extremely understudied, including the mechanisms involved in digestion regulation, continual phagocytosis and phagocytosis-induced phenotypic switching following stroke. Here, we summarize new discoveries related to the molecular mechanisms and multifaceted effects of phagocytosis on brain injury and repair following stroke and highlight the knowledge gaps in poststroke phagocytosis. We suggest that advancing the understanding of poststroke phagocytosis will help identify more biological targets for stroke treatment.